Konsep Bantuan Luar Negeri Cina ke Indonesia sebagai Kedok Investasi (Studi Kasus: Implikasi Pengiriman Tenaga Kerja Asing Cina) - Siregar, Reva Rinanda (Universitas Muhammadiyah Yogyakarta, 2016)
The research about China’s foreign aid for Indonesia is deemed important as the economic growth of China has been skyrocketing for past decades. This growth crowned China as the world’s new economic power. While china keeps on strengthening its economy, several countries in different parts of the world are going through stagnant economic growth. This gives new hopes for many countries to cooperate with China, Indonesia is of no exception, since Indonesia is said to be a promising land of investation.This research utilizes the qualitative method by using case study. The results obtained are, first, for Indonesia, China is bringing positive influence because China is in dire need of raw materials from Indonesia for their industry, where Indonesia is thought as a receiving market of the abundant product from China. Secondly, China left bad influence on local labour competition which creates imbalance between local labour and Chinese labour. Thirdly, China’s foreign aid is not voluntary as these helps are aimed to conduct a one belt diplomacy of China to rule over strategic route of International trading in Indonesia.